Images de l’étrange : Punch ou la re-présentation du paradigme bourgeois - Françoise Baillet (Cahiers Victoriens et Edouardiens)
In the mid-Victorian period, at a time when the forces of respectability were rapidly transforming the British society, Punch, formerly famous for its biting pictorial comment on contemporary events, chose to champion the cause of the increasingly powerful middle-class. Under the pencil of Keene, Leech or du Maurier, the picture became one of the means through which the bourgeois identity was built, defended and promoted. Inadequacies, flaws and imperfections both questioned and constructed the prevailing model, thus « re-presenting » it. More connotative than denotative, the Punch portrait thus carried a significant protective function.On the social front, first, the caricature of the extremes allowed the management of a potentially dangerous otherness. Aristocratic indulgence as well as working-class so-called « degeneration » found themselves relentlessly pinpointed. However, while many Victorians feared a major crisis of the family, the focus was mainly on the private sphere and the drawings played a significant role in the tackling of feminine emancipation. But the concept of identity was also negotiated on the patriotic field and the oddity of the typical Punch stranger became another way for the magazine to reassert the deeply-felt British superiority.